Optimization of inventory management in the peruvian pharmaceutical industry through lean supply chain management methodology in the post-pandemic context - Contreras Alva, Daniela Nicoll (2024)
In the context of the COVID-19 pandemic, the Peruvian pharmaceutical industry faced significant challenges, such as product shortages, lack of medical personnel, and price increases in both public and private establishments. This study proposes a supply management model based on Lean Supply Chain Management (LSCM) methodology for small and medium-sized pharmaceutical enterprises in Peru, aiming to reduce inventory costs and improve service levels. The methodology included data collection and analysis of the current situation of the company, identifying key issues such as ineffective purchasing management, inventory management, non-standardized processes, and inadequate warehouse distribution. The most notable results of the study show a significant improvement in several key indicators. First, the service level increased by 29%, from 61% to 90%. Second, the total cost increased by only 9%, which is a controlled increase considering the benefits obtained. Third, profitability increased by 227%, demonstrating a substantial improvement in profitability. Finally, the net present value (NPV) of the project was $203,936, and the internal rate of return (IRR) reached 80%, suggesting that the implementation of the model is economically viable and highly profitable.